Determinación de la oferta hídrica de la microcuenca del Río Coco en el Cantón Pallatanga, Provincia de Chimborazo. - Carrillo Mejía, Anais Gabriela (2025)
The current study aimed to assess the water supply of the Coco River micro-basin, located in the Pallatanga Canton - Chimborazo province, using the precipitation-runoff method. The study area, covering 97.63 km², is characterized by steep slopes and diverse vegetation. The methodology consisted of three phases: cartographic processing, Curve Number (CN) calculation using HEC-HMS tools, and hydrological modeling. Satellite data and meteorological station data were used, with statistical analysis applied to validate the results. Key findings include a highly responsive precipitation-runoff relationship (55%), indicating limited infiltration capacity. CN values ranged from 30 to 99, influenced by land use and vegetation cover, with denser vegetation leading to reduced runoff. Maximum flows exhibited a consistent increase over the study period, rising from 4.07 m³/s in 2016 to 4.91 m³/s in 2023, reflecting the impact of extreme precipitation events. Similarly, average Flow values increased from 3.13 m³/s in 2016 to 3.88 m³/s in 2023. Additionally, a decrease in water retention capacity was observed, evidenced by greater runoff variability and reduced concentration times (28.32 minutes) between 2017 and 2023. While the micro-basin provides adequate water supply, climate and land use fluctuations necessitate sustainable management strategies. The HEC-HMS model proved effective in evaluating hydrological patterns and projecting future scenarios, serving as a crucial tool for efficient water resource planning and management.